Simulation and validation of the ruminal digestion of carbohydrates in cattle from kinetic parameters obtained by in vitro gas production technique - Silva Cabral,Luciano da (2011)
This study aimed to validate the estimates of the ruminal degradation of total carbohydrates (TC), ruminal and total digestion of fibrous carbohydrates (FC) and microbial nitrogen flow in the abomasum evaluated by in vitro gas production technique (IVGP). Six ruminally and abomasally cannulated steers arranged in a double 3 × 3 latin square were used to measure described parameters with indigestible neutral detergent fiber (INDF) utilization as marker. Total and fibrous carbohydrates degraded in the rumen were estimated through digestion rates obtained for fibrous (FC) and non fibrous carbohydrates (NFC) using in vitro gas production technique, corrected for its respective ruminal and postruminal passage rates. The estimation of the total digestion of FC was done by the sum of ruminal and post-ruminal digestion of these compounds. The microbial nitrogen flow in the abomasum was estimated by the calculating the microbial efficiency of bacteria that ferment FC and NFC, utilizing the microbial growth rate obtained by the ruminal digestion rate for carbohydrate fractions in IVGP. The utilization of the in vitro gas production technique allows obtaining accurate estimates of the ruminal digestion of total carbohydrates, total and ruminal digestion of fiber carbohydrates and microbial protein flow in the abomasum.